Editorial - Masahela, Mary; Calitz, Talita (Critical Studies in Teaching and Learning, 2023)
It gives us great pleasure to get the opportunity to write this editorialatatime when the world continues to be pushed and tossed by the Covid-19 pandemic.Who would have thought that almost two years later countries would be experiencing a fourthwave of the pandemic despite the existence of vaccines!This is confirmation that there is need to consistently do things differently. No more one size fits all.Ugly as this pandemic maybe, it pushes every structure and culture of the world,including the higher education sector,to think out of their comfort box for survival.Intellectuals continue to challenge the current colonised form of operation in the higher education sector as an attempt to dealwithinequalities of the past. All five papers inthis Issueprovide a strong accountof social justice;yettheirfocus is on different concerns about higher education today. In this issue, we see how national politics play outin higher education contexts fromdifferent countries. Of the five papers, only one paper is set in Zimbabwe while the other four are located in South Africa.